Microbiota and Diabetes: Decoding the Gut-Metabolism Link in a Single-Center Study - Nicoleta Mihaela Mindrescu; Cristian Guja; Viorel Jinga; Sorina Ispas; Antoanela Curici; Rucsandra Elena Danciulescu Miulescu; Andreea Nelson Twakor; Anca Pantea Stoian (Gastrointestinal Disorders, 2025)
Background: The relationship between gut microbiota and metabolic health has garnered significant attention in recent years. In this study, we aim to explore the intricate link between gut microbiota and metabolic outcomes, with a focus on lifestyle factors such as smoking, diet, and living environment. Materials and Methods: We investigated the gut microbiota and metabolic profiles of adult patients with type 2 diabetes, all receiving metformin therapy, to assess how lifestyle factors impact metabolic health. Key metabolic parameters and body composition indices were measured, alongside gut microbiota composition. Results: Our cohort included 30 patients, and we identified significant associations between smoking and adverse body composition changes, as well as dietary patterns favoring plant-based foods correlating with improved metabolic outcomes. Urban participants displayed distinct microbiota profiles and metabolic markers compared to their rural counterparts, highlighting the potential influence of environmental factors. Conclusions: The current data does not directly demonstrate a causal link between metformin usage and specific changes in gut microbiota composition. These findings align with the existing literature while providing novel insights into specific population dynamics. Future research should focus on longitudinal studies and interventions targeting the gut microbiota to further unravel its therapeutic potential.